“Linhas de força”: dançares “gengibreiros” reterritorializados pela afrocentricidade - Vilaça, Aline Serzedello Neves (2019)
This dissertation presented in experimental format of an academic-literary essay, bears the title of the choreographic composition that led to the investigations, memories and reflections of the present research and experience report that proposed (re-) knowing and problematizing the methodological, poetic and theoretical details that the work of teaching, research, extension and artistic creation inspired by the popular Afro-Diasporic and Indigenous manifestations carried out by the Gengibre Group (ÁVILA, 2018) between 2005 and 2012 at the Federal University of Viçosa-UFV / MG. Four chapters added to the introduction and final considerations were constructed intermingling poems, songs, photographs, memories, artistic and theoretical quotations concomitant to the process of revisiting the Group's methodologies from the reading of Afrocentricity (ASANTE, 1989) as paradigm, under a female African-diasporic “cosmoperception” (OYEWUMI, 2004), and with critically-analytical Afropperspectivist (NOGUERA, 2015). Conceptually and artistically systematizing inspired by “dançares gengibreiros” in "body and ancestry" (SANTOS, Inaicyra, 2006) that enabled the creation of "Power Line" (2009) and potentiated other artistic-academic teaching products and environments such as the Mandi'o Group (UFGD), Extension Project Aldeia Mangue (UFS), and subjects of the course of Degree in Dance of the UFS like: Africanias, Africanities and Extension and Dance. Reviewing the past to highlight the ways of teaching and character composition, punctuating the fictional making of the Black Performing Arts as a space for activism, denunciation, claim and enunciation of antiracist pedagogies in the fight against epistemicide.